Suitability of Baking Processing for Yak Stomach with Different Muscle Layer Thicknesses - Tianxia ZHAO; Min LIU; Shengsheng LI; Yan ZHANG; Qianglong ZHANG (Shipin gongye ke-ji)
In this study, 17 samples of yak stomach with different muscle layer thickness were taken as the raw meat, and the physicochemical quality, processing quality and eating quality of raw meat and the physicochemical, processing, eating and sensory evaluation differences after baking were analyzed. A comprehensive quality evaluation model Y=0.33A1−0.05A2+0.12A3+0.26A4+0.35A5 (A1~A5 represents b* value, shearing force, foam stability, foaming ability, elasticity) was established. Results showed that those stomach were suitable for roasting, which were the rumem with the muscle layer thickness were 1.5~1.8 cm, the omasum with the muscle layer thickness were 1.0~1.2 cm, and the reticulum with the muscle layer thickness were 0.6~1.2 cm. While the reticulum with the muscle layer thickness was 0.5 cm, the omasum with the muscle layer thickness were 0.5~0.9 cm, and the abomasum with the muscle layer thickness were 0.6~1.2 cm, which were less suitable for roasting. At the same time, the regression equation Y=1.570X−0.258 was established with the overall acceptability as the dependent variable and the comprehensive quality evaluation as the independent variable, and the fitting coefficient of the equation was R2=0.906, which further proved that the comprehensive quality evaluation model could better reflect the suitability of the roast processing of the stomachs with different muscle thicknesses of yak. Through the correlation analysis and comparison of grilling processing indexes and raw meat, it was concluded that the parts with high emulsification activity, high emulsification stability, high protein content and good elasticity were suitable for grilling processing. This study provides a theoretical basis for the deep processing of yak stomachs with different muscle thickness.